2023
DOI: 10.1002/adfm.202312666
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functional Modification for Boosting Power Density of Hydrovoltaic Devices

Yanhui Liu,
Zihao Li,
Liying Wang,
et al.

Abstract: Generating electricity based on the interaction between water and materials is a new green energy harvesting technology. However, the performance based on streaming potential generation is not sufficient to drive microelectronic devices with high power supply demands. In this work, an asymmetric sandwich structure is designed with adjustable performance of hydrovoltaic devices as a power system for micro‐electronic devices. The flexible hydrovoltaic device structure that only consumes renewable energy is low‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In this work, a capacitive evaporative energy device with a sandwich-like structure has been proposed. It consists of a zinc plate, diaphragm, and CC, and then nanoscale materials like carbon black and CNTs are scraped onto the carbon cloth . After testing and characterization, it was found that the incorporation of CNTs significantly enhanced the electrochemical performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a capacitive evaporative energy device with a sandwich-like structure has been proposed. It consists of a zinc plate, diaphragm, and CC, and then nanoscale materials like carbon black and CNTs are scraped onto the carbon cloth . After testing and characterization, it was found that the incorporation of CNTs significantly enhanced the electrochemical performance of the device.…”
Section: Introductionmentioning
confidence: 99%